2017
DOI: 10.1371/journal.pone.0170369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Positive End-Expiratory Pressure on the Sonographic Optic Nerve Sheath Diameter as a Surrogate for Intracranial Pressure during Robot-Assisted Laparoscopic Prostatectomy: A Randomized Controlled Trial

Abstract: BackgroundPositive end-expiratory pressure (PEEP) can increase intracranial pressure. Pneumoperitoneum and the Trendelenburg position are associated with an increased intracranial pressure. We investigated whether PEEP ventilation could additionally influence the sonographic optic nerve sheath diameter as a surrogate for intracranial pressure during pneumoperitoneum combined with the Trendelenburg position in patients undergoing robot-assisted laparoscopic prostatectomy.MethodsAfter anesthetic induction, 38 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
2
12
1
3
Order By: Relevance
“…Although there have been few reports about the effect of PEEP on ONSD in patients during pneumoperitoneum with steep Trendelenburg position, applying PEEP is a still concern because it may aggravate ONSD increase. However, our result showed that 5 cmH 2 O PEEP did not increase ONSD further during pneumoperitoneum with steep Trendelenburg which was consistent with the findings of Chin et al, [25] who underwent 8 cmH 2 O PEEP in RALRP surgery. It might be explained that a transmission of PEEP to the intracranial component was attenuated in patients with decreased lung compliance induced by pneumoperitoneum and steep Trendelenburg position.…”
Section: Discussionsupporting
confidence: 92%
“…Although there have been few reports about the effect of PEEP on ONSD in patients during pneumoperitoneum with steep Trendelenburg position, applying PEEP is a still concern because it may aggravate ONSD increase. However, our result showed that 5 cmH 2 O PEEP did not increase ONSD further during pneumoperitoneum with steep Trendelenburg which was consistent with the findings of Chin et al, [25] who underwent 8 cmH 2 O PEEP in RALRP surgery. It might be explained that a transmission of PEEP to the intracranial component was attenuated in patients with decreased lung compliance induced by pneumoperitoneum and steep Trendelenburg position.…”
Section: Discussionsupporting
confidence: 92%
“…En nuestro estudio realizamos una maniobra de reclutamiento con un incremento de la PEEP de 5 cmH 2 O en 5 cmH 2 O hasta 15 cmH 2 O durante 10 inspiraciones después de 10 minutos de colocar al paciente en posición de Trendelenburg con neumoperitoneo, observando que no se obtuvo diferencia en el DVNO entre el grupo control 0.49 ± 0.06 vs grupo maniobra 0.50 ± 0.05 cm (p = 0.5), al igual que en la comparación del grupo maniobra antes de realizar la manobra de reclutamiento 0.49 ± 0.06 y posterior a la misma 0.49 ± 0.06, siendo nuestros resultados similares a los de Chin JH y colaboradores y Ann Hee You y su equipo; sin embargo, ellos no realizaron una maniobra de reclutamiento, aleatorizaron un grupo control y un grupo con PEEP 8 cmH 2 O y 5 cmH 2 O respectivamente en cada estudio. 29,33 En estudios previos en prostatectomías por robot donde midieron el DVNO, asociaron que un aumento de la PAM de 10 mmHg el DVNO incrementaba 0.023 mm, 22 otro estudio demostró un incremento de 12.5% del DVNO 10 www.medigraphic.org.mx y 30 minutos después de la posición de Trendelenburg y neumoperitoneo. 34 Un estudio de 21 pacientes reveló que tres minutos después de la posición de Trendelenburg y neumoperitoneo el DVNO incrementó 0.4 mm.…”
Section: Discussionunclassified
“…36 Fernando Dip y colaboradores detectaron un incremento de 1 mm del DVNO (p ≤ 0.0001) 37 en nuestro estudio pudimos observar diferencia significativa entre T0 y T3 en el grupo control (p = 0.001) y maniobra (p = 0.001), aunque clínicamente sin impacto a pesar de que en otros estudios no se observaron diferencias significativas en el DVNO. 29,33,38 Encontramos un paciente en el grupo de maniobra que mostró hipertensión intracraneal con un DVNO > 0.55 cm, con un RR = 0.33 (IC 95%: 0.039-2.85 [p = 0.28]). En el grupo control se presentaron tres casos, por lo que podemos deducir que la maniobra de reclutamiento alveolar no tuvo ninguna repercusión a nivel cerebral.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…1); thus, a total of 4 measurements were taken by trained investigators. [13,14] The average of the measured values was used in the analysis. And, 2 investigators measured a random sample of about 25% of the ONSD twice to determine inter-observer variability.…”
Section: Methodsmentioning
confidence: 99%